Der Westen im Osten Deutsches Judentum und jüdische Bildungsreform in Osteuropa (1783-1939) - Grill, Tobias (Jüdische Religion, Geschichte und Kultur, 2013)
Tobias Grill focuses on two groups of German Jews who were active in Eastern Europe between ca. 1839 and 1939: German rabbis and German-Jewish pedagogues. The central question is to what extent both these groups acted as cultural agents regarding the reform of traditional Eastern European-Jewish education system - one of the main realms of Jewish Enlightenment (Haskalah). Insofar, Grill studies how German Jews tried to transfer certain characteristics of the modern German-Jewish Bildungssystem to Eastern European Jewry and how reception and adoption of these elements worked